Kampanye Politik Sebagai Politik Pemasaran : Tinjauan Atas Pemilihan Umum Calon Presiden Indonesia Tahun 2019 - Sukma, Fahrizal; Cangara, Hafied; Saifulloh, Muhammad (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Elections play an important role in the democracy. One of the stages of elections is a political campaign. Political campaigns symbolically unite citizens and leaders in a ritual of debate, discussion and dialogue every four years. However, this can only become a popular myth if political campaigns are not carried out in a democratic manner. In Indonesia, limited campaign time forces election participants to plan effective political campaign strategies through the mass media. This research is an analytical descriptive approach that will describe how the objectives of political campaigns can be achieved within the framework of marketing political communication theory, with a review of the 2019 Presidential Election case. Data and information are collected from Kompas.com, an online media during a certain period. In the 2019 election, the campaign period is very limited. Candidate use all available political resources to campaign and win elections. Based on news analysis on Kompas.com during campaign periode, as an incumbent candidate, Joko Widodo used a campaign to market the programs, such as: digital serving programs, the three magic cards program (Indonesia Smart College Card, Cheap Grocery Cards and Pre-Employment Cards) and infrastructure programs. Meanwhile, the Prabowo Subianto-Sandiaga Salahudin Uno candidate also used the campaign to market their programs, they are strengthening government institutions to prevent corruption and programs to improve Indonesia's economy. Candidate Joko Widodo-Ma'ruf Amin sold his dream, namely